IMPROVING ENGLISH VOCABULARY FOR STUDENTS THROUGH LISTENING TO ENGLISH NEWS - Tran, Yen (International Journal of Language and Literary Studies, 2023)
The major aim of the present research is to investigate the effects of listening to English News on improving the vocabulary of English majors at a university in Vietnam. The researcher called for 60 students to volunteer to take part in the study, 30 of whom were assigned to the experimental group and the other half assigned to the control group. The two groups had to respond to the pre-questionnaire and take the pre-test on vocabulary. The experimental group then entered the experimental process and was asked to listen to English News every day to learn vocabulary. Besides, they did some exercises designed by the researcher related to the English News they heard. Data were collected within ten weeks via the pre-questionnaire, the pre-test, the post-test and the post-questionnaire. The results of the study indicated that the experimental group advanced remarkably in terms of vocabulary compared to the control group. This demonstrated that listening to English News has a positive effect on English majors’ vocabulary. The results of the post-questionnaire also reveal that the students’ feedback on the practice of listening to English News is generally positive.